PROSES DEKANTASI MINYAK ATSIRI DENGAN VARIASI PLAT INTERCEPTOR DALAM DEKANTER - I M. Rajendra; I. A. Anom Arsani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
Decantation process was done to separate oil and water. Mostly, Small Medium Enterprises (SME) use lowtraditional technology as multiple drums. As a result, there is much oil dumped together with wastewater. A betterway to decant oil and water can be done by using an interceptor plate in decanter equipment. This research aims wasto test the performance of decanter with special design by using an interceptor plate. The observation focused ondistance between plates toward the oil content in wastewater, which was measured by its density. Three variables ofplate distance were 10 mm, 20 mm, and 30 mm. Material tests were nilam and clove oil with several concentrationsi.e. 1.96%, 3.85% and 5.66%, and the flow rate was adjusted at 2 liters/minute. The result shown that the interceptorplate with 10mm distance produced wastewater with lower content of oil. In addition, in industry scale test, thedecanter having 10mm distance plate interceptor could reduce oil loss up to 11.8% for nilam and 42.9% for clovecompared to that of multiple drum.